PROLIFERATING INFLORESCENCE MERISTEM, a MADS-Box Gene That Regulates Floral Meristem Identity in Pea - Taylor, Scott A. (American Society of Plant Physiologists, 2002)
SQUAMOSA and APETALA1 are floral meristem identity genes from snapdragon (Antirrhinum majus) and Arabidopsis, respectively. Here, we characterize the floral meristem identity mutation proliferating inflorescence meristem (pim) from pea (Pisum sativum) and show that it corresponds to a defect in the PEAM4 gene, a homolog of SQUAMOSA and APETALA1. The PEAM4 coding region was deleted in the pim-1 allele, and this deletion cosegregated with the pim-1 mutant phenotype. The pim-2 allele carried a nucleotide substitution at a predicted 5′ splice site that resulted in mis-splicing of pim-2 mRNA. PCR products corresponding to unspliced and exon-skipped mRNA species were observed. The pim-1 and pim-2 mutations delayed floral meristem specification and altered floral morphology significantly but had no observable effect on vegetative development. These floral-specific mutant phenotypes and the restriction of PIM gene expression to flowers contrast with other known floral meristem genes in pea that additionally affect vegetative development. The identification of PIM provides an opportunity to compare pathways to flowering in species with different inflorescence architectures.